Difficulties and Strategies on Speaking among English Literature Student of Ahmad Dahlan University: An Interview Study - Vyeri, Al Ariq Rayhan; Bambang Widi Pratolo (EDULANGUE, 2024)
This research aims to identify the difficulties faced by English literature students at Ahmad Dahlan University in developing their English speaking skills and the strategies they employ to overcome those challenges. This qualitative study involved in-depth semi-structured interviews with two 5th semester English literature students. The interview results revealed that speaking anxiety and fear of negative evaluation were common psychological obstacles. However, the specific difficulties of the two participants varied, ranging from vocabulary retrieval, pronunciation, fluency to expanding academic vocabulary. Both utilized individualized strategies tailored to their particular gaps, such as repetition practice or vocabulary expansion through reading. These findings highlight the contextualized, personalized nature of attaining speaking mastery. Supporting students in articulating their specific difficulties and building customized solutions is pivotal. Open dialogue, personalized guidance, and addressing psychological barriers are key to empowering English literature students to achieve academic speaking competence. Keywords: speaking skills, English literature, strategies, difficulties, interviews